(untitled) (Herald of Journalism, 2016)
В статье автор теоретически актуализирует и активизирует такие узнаваемые понятия, как ритм времени, научные стандарты, правдивость и действительность, непосредственно влияющие на современную журналистскую науку и практику. Его мысли о доступных и элитарных текстах, мобилизационной природе действующей аналитической журналистики конкретно транслируют опыт известных отечественных и зарубежных репортеров и спойлеров. По его мнению, покровительница всех других дисциплин - журналистика, должна уметь мыслить и жить в любой обстановке - и в благоприятные, и в трудные времена. The author theoretically updated and activates recognizable such things as a rhythm of time, academic standards, truthfulness and validity directly influencing the modern science and practice ofjournalism. His thoughts on the available texts and elite, th e nature of the current mobilization of analytical journalism specifically translate and transmit the experience of well-known domestic and foreign reporters and spoilers. In his opinion, the patroness of all the other disciplines is journalism that should be able to think and live in any environment, in both good and difficult times.